Efficacy and safety of transcutaneous electrical acupoint stimulation for preoperative anxiety in thoracoscopic surgery: a randomized controlled trial - Jie Zhang; Xindi Wu; Chenni Ju; Subinuer Kurexi; Xiaoxiao Zhou; Ke Wang; Tongyu Chen (Frontiers in Medicine)
BackgroundPatients undergoing video-assisted thoracoscopic surgery (VATS) often experience preoperative anxiety, which can significantly impact the surgical process and postoperative recovery. However, the efficacy of Transcutaneous Electrical Acupoint Stimulation (TEAS) in managing preoperative anxiety in VATS patients is unknown.MethodsA total of 82 patients scheduled for thoracoscopic surgery were randomly divided into TEAS group (n = 41) and sham TEAS (STEAS) group (n = 41). The TEAS/STEAS intervention began 3 days before the thoracoscopic surgery, with one session lasting 30 min per day for three consecutive days. The primary outcome measure will be the change in Generalized Anxiety Disorder Scale scores between the day before surgery and the baseline. Secondary outcome include intraoperative anesthetic consumption, time to postoperative chest tube removal, postoperative analgesic consumption and pain scores, length of postoperative hospital stay, serum concentrations of 5-hydroxytryptamine (5-HT), norepinephrine (NE), and gamma-aminobutyric acid (GABA).ResultsOn the third intervention day, anxiety levels in the TEAS group were significantly lower than in the STEAS group (p < 0.01). TEAS patients required less intraoperative sufentanil, remifentanil, and dexamethasone (p < 0.01). Chest tube removal time and hospital stay were shorter in the TEAS group (p < 0.01). Postoperative meperidine consumption and VAS pain scores were lower in the TEAS group (p < 0.01). Serum 5-HT levels were lower in the TEAS group on day three (p < 0.01), while NE levels remained lower from day three of intervention to postoperative day three (p < 0.05). GABA levels were higher in the TEAS group (p < 0.01).ConclusionTEAS effectively reduces preoperative anxiety, decreases intraoperative anesthetic and anti-inflammatory drug use, shortens postoperative chest tube removal time and hospitalization, and alleviates postoperative pain. These results indicate that TEAS, as an adjunctive therapy, has valuable potential in improving surgical outcomes and postoperative experience for patients with pulmonary nodules.Clinical trial registrationhttps://clinicaltrials.gov, NCT04887090.